Pelatihan Kewirausahaan Berbasis E-Learning Bagi Murid SMK - Dewi, Yuli Kartika; Riza, Fahrul; Jodhinata, Andreas; Anam, Syaiful; Choa, Yeshua Austin Harvey; Tuminem, Hannan Azka (Information Technology and Science (ITScience), 2024)
The ability of institutions organizing Distance Learning (PJJ) to conduct Community Service programs (PkM) online is frequently questioned, notably their effectiveness. The paper seeks to demonstrate that e-learning-based community service initiatives including collaboration among distance learning students, conventional students, lecturers, and partners can produce concrete outcomes. E-learning-based entrepreneurship training was delivered to 20 vocational high school students who were involved in extracurricular entrepreneurship activities. The implementation technique is a mixed approach, with distance learning students acting as presenters, normal students serving as on-site mentors, lecturers designing the curriculum, and schoolteachers monitoring student progress. The training results reveal an increase in entrepreneurial attitude and the ability to produce unique ideas that can be implemented in the field. This conclusion underscores the fact that online community service programs, if well-designed and involving a variety of parties, can be successfully executed and have a good impact on student skill development.